2000
DOI: 10.1093/chromsci/38.4.169
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography--Electrospray Ionization-Mass Spectrometry Study of Ginkgolic Acid in the leaves and Fruits of the Ginkgo Tree (Ginkgo biloba)

Abstract: A method is developed for qualitative analysis of ginkgolic acids in the leaves and fruits of Ginkgo biloba by high-performance liquid chromatography (HPLC)-electrospray ionization-mass spectrometry technique. Negative ionization mode is successful in obtaining a very abundant deprotonated molecule [M - H]-. The mass detection sensitivity is higher than ultraviolet detection but relies heavily on the concentration of acetic acid in the HPLC eluent, which consists of acetonitrile-water-acetic acid. The method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…GAs were the main components of GSEE with antimicrobial activity. Among its four types, namely C13:0, C15:0, C15:1 and C17:1, the most abundant in G. biloba extracts are C15:1 and C17:1 . The HPLC results confirmed the presence of GA C13:0, C15:1, C17:2, C15:0 and C17:1 corresponding to the order of the five peaks in Fig.…”
Section: Resultssupporting
confidence: 91%
“…GAs were the main components of GSEE with antimicrobial activity. Among its four types, namely C13:0, C15:0, C15:1 and C17:1, the most abundant in G. biloba extracts are C15:1 and C17:1 . The HPLC results confirmed the presence of GA C13:0, C15:1, C17:2, C15:0 and C17:1 corresponding to the order of the five peaks in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Fetal-derived Normal Human Astrocytes (NHA, Lonza) were maintained in Astrocyte Growth Medium (AGM, Lonza) supplemented with 0.3% FBS, 30 µl/mL ascorbic acid, 1 µl/mL rhEGF, 30 µg/mL gentamicin, 15 μg/mL amphotericin B, 2.5 µl/mL insulin, and 10 µl/mL L-glutamine. Early passages (1)(2)(3)(4) were used in these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…HPLC-UV has been applied to the analysis of these compounds (Irie et al, 1996), and it has recently been reported that a reversed-phase C 18 column connected in series with a silver (I) loaded cation exchanger column could give good separation of the alkylphenols (van Beek and Wintermans, 2001). HPLC-ESI-MS has also been used to analyse the ginkgolic acids (He et al, 2000;Ndjoko et al, 2000).…”
Section: Introductionmentioning
confidence: 99%